2021
DOI: 10.1002/leg3.110
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide and antinutrient content of whole red haricot bean fermented in salt–sugar and salt‐only solutions

Abstract: Common beans (Phaseolus vulgaris L.) are nutritious and confer numerous health benefits. However, they are also high raffinose family oligosaccharides (RFOs) and antinutrients. Appreciable amounts of RFOs and antinutrients remain after soaking and cooking, causing flatulence and lowered mineral bioavailability to bean consumers. Fermentation has been shown to lower RFOs and antinutrients in bean flours and milk. However, beans are majorly consumed as whole grains. The purpose of this study was to develop a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The main raw materials preferred in fermented plant-based dairy analogue production are categorized as legumes, cereals, and oilseeds (Table 1). A wide variety of plant materials, such as nuts including almond (Bernat et al, 2015), hazelnut (Maleki et al, 2015), and pistachio (Sánchez-Bravo et al, 2020), cereals such as oat (Chen, Wu, et al, 2020) and rice (Ghosh et al, 2015), pseudocereals such as quinoa (Väkeväinen et al, 2020) and buckwheat (Matejčeková et al, 2017), legumes such as soybean (Qian et al, 2020), peanut (Li et al, 2024), and red haricot (Kitum et al, 2022), and seeds including sesame (Calvo-Lerma et al, 2022) and hemp (Nissen et al, 2021), have been utilized for the manufacture of fermented plant-based dairy analogues.…”
Section: Raw Materials Used In the Production Of Fermented Plant-base...mentioning
confidence: 99%
“…The main raw materials preferred in fermented plant-based dairy analogue production are categorized as legumes, cereals, and oilseeds (Table 1). A wide variety of plant materials, such as nuts including almond (Bernat et al, 2015), hazelnut (Maleki et al, 2015), and pistachio (Sánchez-Bravo et al, 2020), cereals such as oat (Chen, Wu, et al, 2020) and rice (Ghosh et al, 2015), pseudocereals such as quinoa (Väkeväinen et al, 2020) and buckwheat (Matejčeková et al, 2017), legumes such as soybean (Qian et al, 2020), peanut (Li et al, 2024), and red haricot (Kitum et al, 2022), and seeds including sesame (Calvo-Lerma et al, 2022) and hemp (Nissen et al, 2021), have been utilized for the manufacture of fermented plant-based dairy analogues.…”
Section: Raw Materials Used In the Production Of Fermented Plant-base...mentioning
confidence: 99%
“…Tannins inhibit hydrolytic enzymes such as trypsin, alpha-amylase, glucoamylase and lipase, and bind not only to proteins but also to minerals and vitamins, making them unusable [68]. Tannins form complexes with proteins through hydrogen bonds through hydroxyl and carbonyl groups, which affect the digestibility of proteins and lead to the inhibition of the utilization of essential amino acids and minerals [69]. Ravoninjatovo et al [70] showed that soaking treatment accelerated the leaching of tannins in KBs, and about 70% of the tannins were lost after soaking for 10 h. The specific action mechanism of tannins in KBs is shown in Figure 4.…”
Section: Tanninmentioning
confidence: 99%
“…Moderate heat treatment will weaken the non-nutritional factors contained in the KBs, gelatinize the carbohydrate components to facilitate digestion and improve the utilization of essential amino acids [32]. The heating method is efficient, simple and low-cost, and has no residue problems, but it is only suitable for heat-unstable non-nutritional factors such as lectins and trypsin inhibitors, and is invalid for heat-stable non-nutritional factors such as phytic acid and saponins [69]. Insufficient heating during the heating process will not eliminate heat-sensitive non-nutritional factors, while excessive heating will destroy arginine, lysine and sulfur-containing amino acids [87].…”
Section: Elimination Of Heat-sensitive Non-nutritional Factorsmentioning
confidence: 99%